The Influence of Transformational Leadership on Employee Job Satisfaction in Foreign Capital Companies in the Bekasi Manufacturing Sector - Chaidar, Diar Fachmi Rachmat (Jurnal Bisnis Mahasiswa, 2022)
The progress of each company is greatly influenced by the leadership role of a company. Therefore, it is very important to determine whether transformational leadership has an impact on the level of employee satisfaction in foreign capital companies in the manufacturing sector in Bekasi. The concepts of descriptive and verification research are used in this research. As a transformational leader, superiors understand various new strategies that are useful for achieving the company's big goals and always try to help and support employee success, according to the research results of respondents to the transformational leadership variable. So, the conclusion is that transformational leadership only affects the level of job satisfaction.